2012
DOI: 10.1596/1813-9450-6147
|View full text |Cite
|
Sign up to set email alerts
|

Does the Minimum Wage Affect Employment? Evidence from the Manufacturing Sector in Indonesia

Abstract: Using Indonesian firm census data, the paper investigates the impacts of minimum wages on employment and wages in Indonesia in the period of 1993-2006. The paper finds that minimum wages have significant and negative employment effects in small firms, but not in large firms. The effects are especially negative among less educated workers who are hit harder by minimum wage rises; workers with high school education and above do not seem affected. Both production and non-production workers lose their manufacturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…These findings suggest that the possibility of spillover effects cannot be easily generalized. The findings for the average effects on formal sector wages are in line with previous studies (for example, Del Carpio et al 2012, Pratomo 2012 and The World Bank 2010) who report wage elasticities between 0.1 and 0.3. Combining this elasticity with actual changes in real wages and the minimum wage demonstrates the economic relevance of the minimum wage policy.…”
Section: Wage Effectssupporting
confidence: 91%
See 2 more Smart Citations
“…These findings suggest that the possibility of spillover effects cannot be easily generalized. The findings for the average effects on formal sector wages are in line with previous studies (for example, Del Carpio et al 2012, Pratomo 2012 and The World Bank 2010) who report wage elasticities between 0.1 and 0.3. Combining this elasticity with actual changes in real wages and the minimum wage demonstrates the economic relevance of the minimum wage policy.…”
Section: Wage Effectssupporting
confidence: 91%
“…However, these studies find that minimum wages increase informality and cause job losses in the formal sector. Negative employment effects in the formal sector are also found in most studies on Indonesia that analyze formal employment by using aggregate data (e.g., Rama 2001, Suryahadi et al 2003, and Del Carpio et al 2012). Our results are also different from those obtained by Chun & Khor (2010), who find negative effects on the probability of being formally employed on an individual level.…”
Section: Employment Effectsmentioning
confidence: 82%
See 1 more Smart Citation
“…TÜİK tarafından açıklanan üretim yöntemine göre 1998 bazlı GSYİH hesapları; Gayrimenkul, Kiralama ve İş Faaliyetlerine ek olarak Konut sahipliği faaliyetini de içermektedir. Ancak SGK istatistik yıllıklarında Konut sahipliği faaliyeti, Gayrimenkul Faaliyetleri grubunda birleşik olarak verildiğinden sektörlere ilişkin 16 İstihdam sayılarının modellenmesinde kayıt dışılığın etkisinin ortadan kaldırılması amacıyla çalışma, SGK'ye kayıtlı hizmet akdi ile bir veya birden fazla işverene bağlı çalışan sigortalı (4/a sigortalıları) sayıları üzerinden yapılmıştır.…”
Section: Veri Seti Ve Yöntemunclassified
“…Large negative effects of the minimum wage increases on formal employment are found in Honduras (Gindling and Terrell 2009), while effects on employment are small in Costa Rica (Gindling and Terrell 2007) and Colombia (Maloney and Núñez 2003) and not statistically significant in Mexico (Bell 1997) and Brazil (Lemos 2009). Much less is known about other developing regions such as Southeast Asia, with the notable exception there of Indonesia, for which various studies have found small negative employment effects after minimum-wage spikes (Rama 2001;Alatas and Cameron 2008;Del Carpio, Nguyen, and Wang 2011). However, despite decreases in formal employment, average employment rates did not change in either Indonesia (Comolla andMello 2011) or Vietnam (Nguyen 2010).…”
Section: Introductionmentioning
confidence: 99%